PENDAMPINGAN MASYARAKAT DALAM PENCEGAHAN STUNTING MELALUI REMUNGGAI DAN VERTIMINAPONIK DI BENGKULU UTARA - Risnita Tri Utami (Fakultas Pertanian, 2025)
Stunting is a serious health problem that affects the growth and development of children under five, and Indonesia has one of the highest prevalence of stunting in Southeast Asia. In an effort to tackle stunting in North Bengkulu Regency, particularly in Suka Maju, Suka Makmur and Karya Pelita villages, various steps have been taken, including education on stunting and the benefits of remunggai, as well as food processing and vertiminaponics training. The education provided has improved the community's understanding of the importance of stunting and the health benefits of remunggai. Training on processing remunggai into additional food products, such as nuggets and milk, as well as vertiminaponik training for simultaneous fish and plant cultivation, received a positive response from the community. This program demonstrates that improving knowledge and skills on nutrition and aquaculture technology can make a significant contribution to stunting prevention and control efforts. Through education, nutritious food processing, and innovations such as vertiminaponik, it is expected to help reduce stunting rates and improve family welfare in the target areas.